2007
DOI: 10.1016/j.vaccine.2007.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced decision support for policy makers using a web interface to health-economic models—Illustrated with a cost-effectiveness analysis of nation-wide infant vaccination with the 7-valent pneumococcal conjugate vaccine in the Netherlands

Abstract: Enhanced decision support for policy makers using a web interface to health-economic models -Illustrated with a cost-effectiveness analysis of nation-wide infant vaccination with the 7-valent pneumococcal conjugate vaccine in the Netherlands Hubben, G.A.A.; Bos, J.M.; Glynn, D.M.; op 't Ende, Anna; van Alphen, L.; Postma, Maarten Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…However, after adjustment for the incidence rates of meningitis and bacteremia and inclusion of the herd protection effect (i.e., reduction in the disease incidence rate from reduced transmission of pneumococci after infant vaccination to nonvaccinated individuals), 62 the ICER was reduced by one-fourth. 58,63 In these studies, vaccine purchasing cost was found to be the most important variable that affects the decision whether to include PCV-7 in the national immunization program in individual countries.…”
Section: 985mentioning
confidence: 99%
“…However, after adjustment for the incidence rates of meningitis and bacteremia and inclusion of the herd protection effect (i.e., reduction in the disease incidence rate from reduced transmission of pneumococci after infant vaccination to nonvaccinated individuals), 62 the ICER was reduced by one-fourth. 58,63 In these studies, vaccine purchasing cost was found to be the most important variable that affects the decision whether to include PCV-7 in the national immunization program in individual countries.…”
Section: 985mentioning
confidence: 99%
“…Recently, new data have been analysed, and updated estimates of cost-effectiveness have been provided. A striking decrease in the cost-effectiveness ratio as compared to the 2001 estimate has been published again in Vaccine (Hubben et al 2007). In particular, base-case cost-effectiveness was estimated at €15,600 per life-year gained.…”
Section: Pneumococcal Vaccinementioning
confidence: 91%
“…In particular, (1) oneoff vaccination at 14 months, (2) two doses at 5 and 6 months, and (3) three doses very early in infancy (2, 3 and 4 months) were all assumed to provide similar longterm protection (in the model assumed at 90% effectiveness for a duration of 20 years, as seen for other conjugate vaccines). In an aggregate analysis-each scenario in turn being compared with "doing-nothing"-all scenarios provided acceptable cost-effectiveness ratios per life-year gained (Table 2) if we recall that for the Netherlands once a threshold has been suggested at €20,000 per life-year gained (Hubben et al 2007). This might be labelled "the aggregate approach", also sometimes referred to as calculating average cost-effectiveness.…”
Section: Meningococcal C Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…As data showing disease reduction in unvaccinated cohorts began to emerge, the earlier models were revised to include herd effects. This led to PCV7 becoming cost effective and eventually to cost-savings in markets where PCV7 penetration was high over a longer duration and led to a substantial herd effect [19,[34][35][36][37][38].…”
Section: Reviewmentioning
confidence: 99%